The language of religion: The reversion of the ezan from Turkish to Arabic - KOÇYİĞİT, ÖMER (Leiden University Press, 2023)
The Republic of Turkey was founded a hundred years ago on 29 October 1923. Turkey holds a unique position between Europe and the Middle East. It continues to captivate international attention, evoking hopes and fears in the hearts and minds of contemporary observers. As a critical commemoration of its centenary, this book presents a mosaic of one hundred carefully curated fragments by expert authors, shedding light on politics, economy, society, culture, gender, and arts in a hundred years of Turkey. Each fragment offers a glimpse into a specific aspect of Turkey’s development, revealing the complexities of Turkey’s historical reality. Through exhibiting a diverse range of historical sources like laws, speeches, essays, letters, newspaper articles, poems, songs, memoirs, photos, posters, maps, and diagrams, each fragment brings the voices and images of Turkey’s past and present to readers. A Hundred Years of Republican Turkey: A History in a Hundred Fragments is an invaluable resource for researchers, educators, students, and anyone interested in Turkey’s fascinating history since 1923.